Therapeutic management in histamine intolerance: an integrative review - Sousa, Iori Caio Castelos de; Souza , Geovana Martins de; Andrade, Eva Débora de Oliveira; Monteiro, Norberto; Machado, Richele Janaína de Araújo (Journal of Health & Biological Sciences, 2025)
Objective: we conducted a literature survey on nutritional strategies for the management of histamine intolerance to produce an integrative literature review in databases. Methodology: After removing all duplicates, relevant articles were selected in three distinct phases. These phases consist of a gradual process of article selection and verification and narrowing of the inclusion criteria until reaching the proposed result. Original articles published in the last five years focusing on strategies for the treatment of histamine intolerance were included. Results: After research and tabulation of data, it was demonstrated that a low-histamine diet effectively reduces gastrointestinal and systemic symptoms in more than 70% of patients with histamine intolerance. Furthermore, DAO supplementation proved to be a complementary alternative for patients with refractory symptoms. Conclusion: The study is of great relevance in clinical practice and a guide for patients. On the other hand, additional studies are needed to validate diagnostic biomarkers, consolidate clinical guidelines and explore personalized approaches that promote intestinal health and overall well-being of patients.